Diminution in value of works due to deffects - Hashim, Norhaibati (2011)
Defect is one of the major causes of dispute in construction projects. In the context of construction, a defect or defective work is work that is not in accordance with the contract. It is common for standard forms of contract to make express provision for dealing with the defects or defective work. This provision provides the action that can be taken by the employer in the event of contractor’s default in rectifying the defects. One of the alternative is the employer may ascertain the diminution in value of the works if in his opinion that the defects should be inconvenient to be rectified. However, there is no definition of an appropriate deduction and rule to assess the diminution in value of the said works. At what point is the deduction is determined? Hence, this research intends to identify the basis of how the courts measure the diminution in value for construction defects. This research was carried out mainly through documentary analysis of law cases and law reports on diminution in value. Results show that there are several measures that the courts used in assessing the diminution in value. They are based on the difference between the value of the buildings without the defects and the value with the defects, cost of repair, cost of reinstatement and cost of rectification. The date of assessment is also different for the cases analyzed. It is recommended that the principle to ascertain the diminution in value of the works due to the defects should be included in the standard form of contract. The purpose is to provide the guideline on how to measure the diminution in value of defective works.